ESTIMATION OF EQUATIONS COST MODEL FOR REARING REPLACEMENT DAIRY COWS. - Arifin, Melinda Aulia; Hadiana, Muhammad Hasan; Firmansyah, Cecep Firmansyah; Daud, Andre Rivianda (Fakultas Peternakan, Universitas Padjadjaran, 2024)
A research was conducted to generate a mathematical model for estimating the rearing cost of replacement dairy cattle. This research uses a survey method to collect data regarding farmer expenditures in raising young dairy cattle. Data collection involved 67 farmer who kept 231 replacement dairy cows with various ages, from birth up to two years of age. Data analysis used linear regression to estimate an equation model for describe a causal relationship between the partial total cost (TCp) with the period of rearing the cattle (q). The analysis performs two model equation namely quadratic and cubic cost function. The second model performs a goodness of fit better, with an S-shaped curve, . Analysis of variance result in the R2 of 0.67. Based on the estimated cost equation model above, total cash expenditure for two-year-old pregnant heifers reached IDR 15,565,800. If the opportunity cost of a calf is included in the cost calculation, the cost will increase to IDR 19,102,800. Compared to the local price for two-year-old heifers, farmers still have a price margin of IDR 6,211,200.Keywords: replacement cows, total cost partially, cost function